Sosialisasi Peran Paralegal dalam Memberikan Bantuan Hukum Non Litigasi di Desa Sindangbarang, Jalaksana, Kuningan - Kanda Ramandana; Ira Ghina Salsabila; Iman Jalaludin Rifa’i; Haris Budiman (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
The participation of the community in realizing a village free from drugs and online gambling is crucial. Therefore, this legal counseling activity was carried out as an effort to provide a better understanding of the dangers of drugs and online gambling, as well as the importance of legal assistance for the community. This activity involved students from the Faculty of Law, Kuningan University who acted as facilitators in providing legal counseling to the community of Sindangbarang Village. The implementation method used was a legal counseling method with a discussion and question and answer approach. The results of this activity showed an increase in public understanding of the dangers of drugs and online gambling, as well as the importance of legal assistance for the community. This activity also provided an understanding of the role of the community in realizing a village free from drugs and online gambling. This activity is expected to be an initial step in creating a more law-conscious and safe environment for the people of Sindangbarang Village.